Labor pedagogy: polish labor market under the influence of european integration - Kohut Svitlana (Borys Grinchenko Kyiv Metropolitan University, 2018)
Experts determine the changes in the labor market and employment as one of the peculiarities of the European integration process of the Republic of Poland. The article indicates trends that led to changes in the labor market and employment, focusing on a concise analysis of the threats and challenges that Polish society faced.It is indicated that trends, challenges and threats, their extensive diagnostics and theoretical understanding became the subject of studies of labor pedagogy. This is a branch of pedagogical knowledge that studies issues of education in conjunction with human professional work, develops qualification frameworks, modular programs of professional learning, professional education programs, practical projects for the further development of professional training, retraining, and improvement of specialists for the free labor market. The new forms of employment, including outsourcing, freelance, competition for the place of work (as the basis for the development of new competencies) relate to positive phenomena in the labor market during the investigated period. The threats that arise in the field of employment have also been reconsidered. In particular, such forms of the functioning of the individual in the work environment as workaholism, mobbing, professional stress, high unemployment level.Studying of the Polish experience of applied approaches in the research of these phenomena has a direct impact on: the formation of the goals of professional education of specialists in the context of Ukraine's Eurointegration course; the development of flexible content in order to adapt to the needs of the modern economy, to the various forms of population's engagement (especially unemployed one) to different types of education and social inclusion.